If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6 = 2x + -3 Combine like terms: 3 + -6 = -3 -3 = 2x + -3 Reorder the terms: -3 = -3 + 2x Add '3' to each side of the equation. -3 + 3 = -3 + 3 + 2x Combine like terms: -3 + 3 = 0 0 = -3 + 3 + 2x Combine like terms: -3 + 3 = 0 0 = 0 + 2x 0 = 2x Solving 0 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 0 + -2x = 2x + -2x Remove the zero: -2x = 2x + -2x Combine like terms: 2x + -2x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| n/2=-1/34 | | 4+4x+3x=-10 | | Y^2=16/64 | | -.8x=24 | | Q^2=225 | | |1/3d-6=15| | | -5x+1=-6x-6 | | 5(x+1)=63-2x-2x | | 50=6(n+8)-(8n-6) | | 1-x+7x=55 | | -7x+4+2x=39 | | -33=-3(r+5)-3(-6r+6) | | 3x^4+7x^3+18x=0 | | 1-7x+3x=-27 | | 3b-5z=8 | | 19=3(g+3)+1 | | -1/12x=1/4 | | -38+6x=4(8x-3) | | 4(x-1)-2(3x-2)=3-5(x-3) | | 2(p+2)=16 | | 7/2=21/6 | | 18+5b=3b | | 2(c+14)=37 | | -(8+7p)=-6p-13 | | 11=-5x-5x-9 | | =13-v | | g/2-4g=20 | | (-2/5)x=-4/15 | | h-3/3=4 | | 5(6+5a)=4a-12 | | 7n+12*13n-16*6n=360 | | (7n+12)(13n-16)(6n)=360 |